Perfil físico de los esgrimistas en la modalidad sable pre-seleccionados para participar en los JJOO de la juventud 2018 del club de esgrima casa González 2015 (2015)
The intervention of specialized programs according to the specific load in sports and sport planning long-term strategies are processes that strengthen sports in fencing, taking into account the load distribution 60% technical / tactical and 40% physical, reflecting the dependence of the above two factors. In addition, the sport selection must be designed under the specific criteria of sport and understand the changes in the training of a fencer, according to the development of sport nationally and internationally. Corroborating this theory a training program was conducted on a sample comprised 14 children and adolescents between 10 and 17 years of age (6 women and 8 men) Gonzalez Fencing Club House Plata degree; resulting in improved testing representative 10x5 meters of 24.8% (corresponding to 4 seconds) and average group of women. In men and group 6 seconds corresponding to 39.7% and in the Test Course Navette an improvement of 44.4% (corresponding to 3 minutes), on average the group of women and men a group of three minutes corresponding improvement was found at 31.5 %. The results obtained in the test Galton between the pre-test and post-test, an improvement is seen in the reaction rate, significant 31.6% (corresponding to 8 cm), average women's group. In men a group improved 7 cm corresponding to 27.6% was found. Concluding that the redesign of the training plan for athletes focused on speed endurance, strength endurance and explosive strength, in order to prolong the time based combat the large aerobic capacity necessary fencers.